Prawo do prywatności (zagadnienia wybrane) - Mielnik, Zbyszko (Wydział Prawa i Administracji UAM, 1996)
Article as a whole examines aspects of privacy rights. It consists of the three parts. The first one surveys the geography of the subject. Starting with the definition and the scope of privacy, it will then look at the way in which the aspects of privacy developed. The second one corncens the protection of privacy given by the instruments of international law to which POLAND is a party. It examines not only the judgements of European Court of Human Righst but the decisions of European Comission on Human Rights as well. The third one surveys the polish law concering the privacy and the protection given by it. It also compares whether the regulation of polish law concering privacy meet requirements of European Convention on Human Rights.
The right of property